Study of trend of links between scientific community and enterprises - Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
There exists actually many studies of research works which enhance the science-technology (S&T) roles but pay least attention to the role of the scientific community, where scientific knowledge is produced, and business community, where S&T research results get applied, brought into production and turn back to serve the socio-economic life. In this connection, there exist some topics for research. This paper deals with the two main contents: i) Concepts of links between the scientific community and enterprises, and ii) Trends of links between the scientific community and enterprises Code: 13071401 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">